Pattern, clinical features and response to corticoids of glomerular diseases in a Brazilian population: an analytical cross-sectional study - Queiroz, Anaiara Lucena; Barreto, Dulce Maria Sousa; Silva Junior, Geraldo Bezerra da; Tavares Neto, José Edísio da Silva; Costa, Francisco Israel; Patrocínio, Régia Maria do Socorro Vidal; Daher, Elizabeth De Francesco; Almeida, Paulo Roberto Carvalho de (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Glomerular disease registries are increasing all around the world. The aim of this study was to evaluate the clinical characteristics and treatment response among patients with glo-merular diseases followed up in a tertiary hospital in Brazil. DESIGN AND SETTING: Analytical cross-sectional study; tertiary-level public hospital. METHODS: This study included patients with glomerular diseases followed up at a tertiary hospital in Fortaleza, northeastern Brazil. Clinical and laboratory data on each patient were registered. The response to specific treatment was evaluated after 3, 6 and 12 months. RESULTS: The study included 168 patients of mean age 37 ± 14 years. The most prevalent glomerular diseases were focal segmental glomerulosclerosis [FSGS] (19.6%), minimal change disease [MCD] (17.9%), membranous nephropathy [MN] (16.7%) and lupus nephritis [LN] (11.9%). The main clinical presenta-tions were nephrotic proteinuria (67.3%) and renal insufficiency (17.9%). The mean proteinuria value de-creased after the treatment began. Regarding 24-hour proteinuria on admission, there was no significant difference between patients with a good response and those with no response (7,448 ± 5,056 versus 6,448 ± 4,251 mg/24 h, P = 0.29). The glomerular disease with the highest remission rate was MCD (92%). Absence of interstitial fibrosis presented a strong correlation with remission (remission in patients without fibrosis = 83.4% versus 16.3% in those with fibrosis, P = 0.001). CONCLUSIONS: The present study found that the most frequent glomerular disease was FSGS, followed by MCD, MN and LN. The presence of interstitial fibrosis was a predictor of poor therapeutic response.